(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Contemporary international law is concerned with providing protection for the atmosphere, for it is one of the main factors that ensures the continuation of life on the planet and a common heritage of humanity that is passed down through generations. What is the legal nature of the atmosphere and what is the responsibility of the international community in protecting it? It is becoming increasingly difficult to answer the previous questions in light of the tremendous technological development of our time, which has created a lot of electromagnetic radiation produced by all countries of the world and is likely to harm the atmosphere as it is affected by natural factors, especially the ultraviolet rays of the sun. The current research attempts to discuss the role of international law in protecting the atmosphere from electromagnetic radiation based on the role played by international agreements in the field of reducing gas emissions that cause damage to the atmosphere, especially the damage to the depletion of the ozone layer and the rise in temperatures that lead to climate change on the surface of the globe.